Protective lipid-lowering variants in healthy older individuals without coronary heart disease. Issue 2 (2nd August 2021) - Lacaze, Paul; Riaz, Moeen; Sebra, Robert; Hooper, Amanda J; Pang, Jing; Tiller, Jane; Polekhina, Galina; Tonkin, Andrew; Reid, Chris; Zoungas, Sophia; Murray, Anne M; Nicholls, Stephen; et al.
Abstract : Objective: Genetic variants that disrupt the function of the PCSK9 (proprotein convertase subtilisin kexin type 9) and APOB (apolipoprotein B)genes result in lower serum low-density lipoprotein cholesterol (LDL-C) levels and subsequently confer protection against coronary heart disease (CHD). The objective of this study was to measure the prevalence and selective advantage of such variants among healthy older individuals without a history of CHD. Methods: We performed targeted sequencing of the PCSK9 and APOB genes in 13 131 healthy individuals without CHD aged 70 years or older enrolled into the ASPirin in Reducing Events in the Elderly trial. We detected variants in the PCSK9 and APOB genes with predicted loss-of-function. We associated variant carrier status with serum LDL-C and total cholesterol (TC) levels at the time of study enrolment, adjusting for statin use. Results: We detected 22 different rare PCSK9/APOB candidate variants with putative lipid-lowering effect, carried by 104 participants (carrier rate 1 in 126). Serum LDL-C and TC concentrations for rare PCSK9/APOB variant carriers were consistently lower than non-carriers. Rare variant carrier status was associated with 19.4 mg/dL (14.6%) lower LDL-C, compared with non-carriers (p≤0.001, adjusted for statin use). Statin prescriptions were less prevalent in rare variant carriers (16%) than non-carriers (35%). The more common PCSK9 R46L variant (rs11591147-T) was associated with 15.5 mg/dL (11.8%) lower LDL-C in heterozygotes, and 25.2 mg/dL (19.2%) lower LDL-C in homozygotes (both p≤0.001). Conclusions: Lipid-lowering genetic variants are carried by healthy older individuals and contribute to CHD-free survival. Trial registration number: NCT01038583 .